Online Education as a New Paradigm: Challenge and Challenges in the 21st Century (Docentes 2.0 Journal, 2025)
Education as a fundamental pillar of social progress tends to progress rapidly today, being a challenge in the 21st century; it had influence and benefit during the COVID-19 pandemic, based on gender and school performance, where the perception of virtual learning facilitated the understanding of complex and interactive concepts. The study aimed to analyze from various perspectives and research how students perceive and adapt to an online education based on challenges. To carry out the research, the systematic review technique with a documentary-type design was used, carried out by searching for previous studies of scientific articles published in reliable databases such as Scopus, Wos, Scielo, Science Direct, Proques A.T. & A. D., Proques A. & H. D., Education Source, which guarantees the reliability of various collections and publications of complete and quality scientific literature with a time equal to or greater than 5 years after its publication, applying for this purpose, filters and logical connectors: AND-OR-NOT and keywords, from which through the PRISMA 2020 method and flowcharts only 27 scientific articles were extracted for analysis. Their results highlight certain qualities of students who focus their attention and tend to adapt to virtual education, experiencing new changes in the way they learn from various digital platforms. It is also concluded that virtuality is viable and can be effective if appropriate strategies are implemented to adapt their learning habits and the way they interact with educational content.
Keywords: Education; online education; challenges; pedagogical practices